Encouraging prosocial behavior from older adults through robot teleoperation: A feasibility study - Maalouly, Elie; Hirano, Takashi; Yamazaki, Ryuji; Nishio, Shuichi; Ishiguro, Hiroshi (Frontiers in Computer Science, 2023)
In Japan, the social climate for older people has been worse as a result of the coronavirus's spread and the increasing isolation of adults who are increasingly unable to engage in prosocial behavior through work and volunteering. This is detrimental to the physical and mental well-being of older adults. In this study, we look into robot teleoperation for older adults as a viable way to deal with these issues and overcome the barriers preventing older adults from engaging in prosocial behavior. We designed and tested a remote-control approach for dialogue agents that is appropriate for older adults as well as evaluating their impressions in a real-world setting. Twelve older adults participated in experiments in two separate locations, a children's center and the city ward office, where they could remotely teleoperate a robot and have conversations with the visitors. In the city ward office, the older adults had a conversation with the visitors and gave them information and trivia quizzes about the city. In the children's center, older adults had conversations with children regarding their age, family, their likes, and dislikes. A questionnaire and interview were set up after the experiments to understand their impressions of the system and to clarify how older adults feel about certain issues regarding remote-controlled work, starting a new job, social interaction, to what extent have older adults been affected by the pandemic, how and in what ways has it affected their involvement in society, and whether teleoperating a robot can be a suitable approach to encourage prosocial behavior from them through volunteer work and social engagement. Older adults showed readiness to engage in volunteer work and were able to successfully engage in prosocial behavior through remote-controlling a robot. The system seems to be effective at easing the physical barriers preventing older adults from engaging in volunteer work, which have worsened since the spread of COVID-19.